Dental health of the historical adult population of Tver (12th-19th centuries, European Russia): Report 2 (Bulletin of the International Association for Paleodontology, 2023)
This is the second article of the series with the analysis of all known to-date data on the dental health of the historical adult population of Tver (12th-19th centuries, European Russia). Report 2 covers the antemortem tooth loss